A Note on the Equivalence of Methods to finding Nonclassical Determining Equations. Issue 3 (3rd July 2019) - Goard, J.
Abstract : In this note we prove that the method of Bîlã and Niesen to determine nonclassical determining equations is equivalent to that of Nucci's method with heir-equations and thus in general is equivalent to using an appropriate form of generalised conditional symmetry.